MESSAGE IN A BOTTLE: IN VITRO UPREGULATION OF BIOACTIVES IN TWO AROMATIC MEDICINAL CAPE PLANTS - Makunga, N.; Van Staden, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The aromatic plants, Salvia africana-lutea and Pelargonium sidoides are highly valued as medicinal plants in South Africa. P. sidoides is becoming increasingly sought after for its coumarin compounds which are reputed as being effective against bronchial infections. This particular species is now threatened by uncontrolled harvesting for both local herbal markets and international export. Salvia africana-lutea is endemic to coastal regions of the Cape Floristic Region which are fast becoming more urbanized. At present, there are no alternative sources of the active compounds of both Salvia africana-lutea and Pelargonium sidoides. Through biotechnological manipulation, both transgenic and non-transgenic organ cultures are available to study secondary metabolism. Metabolite profiling through GCMS, LCMS and NMR indicated interesting changes in the chemical footprints. Micropropagation does not adversely alter the complexity of essential oils produced by these plants. All S. africana-lutea methanol: dichloromethane (1:1 v/v) extracts were effective against Fusarium verticilliodes (a plant pathogen) (MIC range of 20 µg/ ml to 320 µg/ml). Extracts analysed via GCMS exhibited a larger subset of new compounds which were not normally present in non-transgenic cultures with an increased production of caffeic acid derivatives, fatty acids and plant sterols. Differences of rol transgene integration account for intra- and inter-clonal chemical variation in P. sidoides clones as each rol gene has an individual impact on the hairy root traits. Multiple copy insertions may be responsible for changes in metabolic flux. Many of the putatively identified compounds from both species are useful for the pharmaceutical and agrochemical industries